Iskanje ciljnih segmentov za ozaveščanje o depresiji s pomočjo odločitvenih dreves - Cugmas, Marjan (Teorija in praksa, 2015)
The purpose of this paper is to determine whether decision trees can be used to distinguish between those who are more and those who are less prone to depression and mental ill-being based on demographic and some other identifiable characteristics of individuals. Using decision trees we wanted to find segments which could be targeted in awareness-raising programs about depression. By analysing data from the European Social Survey in 2012 for Slovenia, we identified four groups at a greater risk of depression: young unemployed, unemployed passive, older people and women older than 52 years. Decision trees are also shown for finding target segments in the field of mental well-being. The results confirm the findings of previous studies.
Keywords: Classification; Depresija; Depression; Duševno zdravje; Klasifikacija; Mental health; Prevention; Preventiva; raziskave